2017
DOI: 10.1515/agp-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Description of the lower jaws of Baculites from the Upper Cretaceous U.S. Western Interior

Abstract: We report the discovery of lower jaws of Baculites (Ammonoidea) from the Upper Cretaceous U.S. Western Interior. In the lower Campanian Smoky Hill Chalk Member of the Niobrara Chalk of Kansas, most of the jaws occur as isolated elements. Based on their age, they probably belong to Baculites sp. (smooth). They conform to the description of rugaptychus, and are ornamented with coarse rugae on their ventral side. One specimen is preserved inside a small fecal pellet that was probably produced by a fish. Another s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The main arguments against the hypothesis of a secondary opercular function of aptychi were based on the misfit between the ammonite apertures and associated aptychi. For instance, Morton (1973) found that the aptychi of Jurassic Sonninia did not provide a perfect fit to the aperture; the same was stated for Late Cretaceous Baculites by Larson & Landman (2017). As to scaphitid aptychi, Lehmann (1972) noted a significant dissimilarity between the shape and size of the aptychus and whorl section near the aperture in a specimen of Jeletzkytes nebrascensis (Owen, 1852) which served as the basis for the interpretation of aptychi as jaw elements by Meek & Hayden (1864) and Meek (1876).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The main arguments against the hypothesis of a secondary opercular function of aptychi were based on the misfit between the ammonite apertures and associated aptychi. For instance, Morton (1973) found that the aptychi of Jurassic Sonninia did not provide a perfect fit to the aperture; the same was stated for Late Cretaceous Baculites by Larson & Landman (2017). As to scaphitid aptychi, Lehmann (1972) noted a significant dissimilarity between the shape and size of the aptychus and whorl section near the aperture in a specimen of Jeletzkytes nebrascensis (Owen, 1852) which served as the basis for the interpretation of aptychi as jaw elements by Meek & Hayden (1864) and Meek (1876).…”
Section: Discussionmentioning
confidence: 88%
“…8), offers an opportunity for testing the opercular hypothesis for Hoploscaphites constrictus crassus . The main arguments used in previous discussions on the subject based on testing potential matches or mismatches between the shape and size of the ammonite apertures with those of the associated aptychi (Trauth 1927–1936; Morton 1973; Lehmann & Kulicki 1990; Keupp & Mitta 2013; Larson & Landman 2017). Accordingly, lines 1–6, previously identified in the specimen ZPAL Am.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outline of the lower jaw spread open matches the shape of the whorl cross section ( Baculites , Scaphites ), which led to the suggestion that this structure had an opercular function. By contrast, Larson & Landman (2017) and Landman & Waage (1993 b ) argued that the jaws of Baculites , even when fully splayed out, did not touch the inner surface of the conch tube. Accordingly, they rejected an operculum function of the lower jaw in Baculites .…”
Section: Soft Body Reconstructionmentioning
confidence: 94%